Effect of ginsenosides on microbial community and enzyme activity in continuous cropping soil of ginseng - Miao, Xinyue; Wang, Ergang; Zhou, Yi; Zhan, Yu; Yan, Ning; Chen, Changbao; Li, Qiong (Frontiers in Microbiology, 2023)
Root exudates contain plant metabolites secreted by the roots into the soil, such as ginsenosides secreted by the ginseng root. However, little is known about ginseng root exudate and its impact on the chemical and microbial properties of soil. In this study, the effect of increasing concentrations of ginsenosides on the chemical and microbial properties of soil was tested. Chemical analysis and high-throughput sequencing techniques were used to evaluate the soil chemical properties and microbial characteristics following exogenous application of 0.1 mg·L-1, 1 mg·L-1, and 10 mg·L-1 ginsenosides. Ginsenosides application significantly altered soil enzyme activities; SOM-dominated physicochemical properties were significantly reduced which altered the composition and structure of the soil microbial community. In particular, treatment with 10 mg∙L-1 ginsenosides significantly increased the relative abundance of pathogenic fungi such as Fusarium, Gibberella and Neocosmospora. These findings indicate that ginsenosides in root exudates are important factors that may lead to increased deterioration of soil during ginseng cultivation and provided new research direction for the subsequent study on the mechanism of interaction between ginsenosides and soil microbial communities.